SHED‐derived exosomes improve the repair capacity and osteogenesis potential of hPDLCs. (6th April 2022) - Wang, Menghong; Li, Jie; Ye, Yanyan; Chen, Duanjing; Song, Jinlin
Abstract: Objective: Exosomes secreted by stem cells are recognized as a critical component in tissue regeneration during stem cell‐based therapy. Considering the limited sources and bone regeneration efficiency of human periodontal ligament cells (hPDLCs), we explored whether exosomes secreted by stem cells from human exfoliated deciduous teeth (SHED‐exo) could improve the pluripotency and regenerative potential of hPDLCs. Methods and Materials: In hPDLCs, cell proliferation, migration, cell cycle, apoptosis, and osteogenic differentiation were detected after cells were exposed to SHED‐exo (SHED‐exo group), blank (control group), or control supernatant without exo (Csup group), via CCK‐8, scratch analysis, flow cytometric, real‐time PCR, and so on. Exosomes sequencing was performed to compare and analyze miRNAs contented in SHED‐exo and hPDLC‐exo. Results: As compared to control or Csup, SHED‐exo significantly increased migration, apoptosis, and proliferation, promoted cell cycle transition from G1 to S phase in hPDLCs, and enhanced Runx2 expression and mineralization. In addition, it may be explained by the significant differences in miRNA contented in SHED‐exo and hPDLC‐exo. Conclusion: Exosomes from SHED can improve cell proliferation, migration, cell cycle, apoptosis, and osteogenic differentiation of hPDLCs, which highlights the therapeutic value of this bioactive component in the regeneration of periodontal tissues using hPDLCs in clinical practice.